The adaptable coach - a critical review of the practical implications for traditional and constraints-led approaches in sport coaching - Lindsay, R.; Spittle, M. (International Journal of Sports Science & Coaching, 2024)
Coaches are faced with navigating a complex and dynamic environment that requires the wise and measured management of numerous competing factors. Traditional and contemporary approaches are often contrasted, with traditional approaches thought to be beneficial for outcomes like speed of skill acquisition but criticised for being overly prescriptive, and contemporary approaches praised for facilitating individualised learning and transferrable skillsets. We contend that the task for coaches is not deciding which approach is "better" and strictly conforming to one approach, rather it is determining which approach or learning principles best suit the athlete's learning requirements. Coaching is not an exact science, it is an art, in which skilled coaches need to be open, adaptable, and flexible in their approach, constantly considering the complexities of the wider coaching process. In this article, we discuss how coaching practices have the potential to be enhanced by integrating key principles from both traditional and contemporary (CLA) approaches to adapt practice to the emerging situation and meet the skill development needs of their athletes while considering the intricacies and subtleties that typify real-world coaching environments.